Christian Reminiscences in Live Speech (in Old Believers’ Subdialects of Prikamye) - I. A. Podyukov (Научный диалог)
The article brings about the issue of book reminiscences in the live speech of the bearers of the Old Believers’ tradition of Prikamye. Reflecting religious consciousness, they have dogmas about the meaning of life and laws of morality; reveal the essence of ethical guidance. Attention is paid to the functions of reminiscences, the ways of their use: introduction of the name of a Christian character or the name of a sacred object into the statement, inclusion of the names of precedential artifacts in live speech, the use of phraseological units from the texts of traditional literature and allusions. The novelty of the study is seen in the fact that the Old Believers actively used references to the biblical, hagiographic and apocryphal texts. Book inclusions are endowed with worldview and didactic meanings; they express an analogy between the facts of Christian history and the phenomena of real life. It is proved that the use of elements of religious texts revives the meanings of these texts in the mind of a native speaker, endows oral speech with the properties of intertextuality. The use of religious reminiscences is characterized by their broad variation, due to the conditions of oral dialect communication, and reflects the decline of religious literacy. The relevance of the study is conditioned by the fact that the images of book and written culture involved in everyday speech remain a littlestudied means of expressing the complex world of feelings and emotional experiences of a believer.